Solid Lipid Nanoparticles for Skin Delivery of Trans-Resveratrol: Impact of Preparation Methods on Formulation Stability - Cruz, Andressa Tardim [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Duarte, Jonatas Lobato [UNESP]; Guillot, Antonio José; Pérez-García, Alberto; Melero, Ana; Chorilli, Marlus [UNESP] (MDPI, 2025)
Trans-resveratrol (RES) is a natural polyphenol known for its antioxidant, anti-inflammatory, and anti-aging properties, making it highly valuable in cosmetic applications. Solid lipid nanoparticles (SLNs) offer a promising solution to enhance RES’s stability and cutaneous availability. This study aimed to develop and characterize SLNs encapsulating RES for enhanced skin delivery. Multiple methodologies were evaluated to determine the impact of preparation methods on formulation stability. SLNs were formulated using stearic acid, soy phosphatidylcholine, polysorbate 80, cetyltrimethylammonium bromide, and poloxamer 407, with variations in heating temperatures and homogenization techniques. Stability assessments were conducted over 90 days, examining organoleptic properties of the hydrodynamic diameter, polydispersity index, and zeta potential. Encapsulation efficiency and skin permeation studies were performed to investigate the efficacy of SLNs in delivering RES. Results demonstrated that formulations prepared with Ultra Turrax at 24,000 rpm and heating at higher temperatures exhibited enhanced stability and smaller particle sizes. The selected formulations, F1 (prepared at 80 °C) and F2 (prepared at 70 °C) presented encapsulation efficiencies of 70% and 72%, respectively. Skin permeation studies confirmed the ability of SLNs to facilitate RES delivery through the skin. The study concludes that SLNs are suitable carriers for RES skin delivery, offering improved stability and sustained release, thus representing a promising approach for topical applications to leverage RES’s cutaneous therapeutic benefits.